Feeding Management of Super Intensive Tilapia Fish (Oreochromis niloticus) Culture - Alhijrah, Muhammad Rifki; Scabra, Andre Rachmat (Jurnal Media Akuakultur Indonesia, 2023)
Tilapia is a commodity that has a high selling value. The demand for tilapia from year to year continues to increase, because this fish is popular and is also considered to be aquatic chicken, even this has been known as aquatic turkey. This Field Work Practice aims to find out the Management of Super Intensive Nila Tilapia (Oreochromis niloticus) Feeding in Tambak Teratak Village, North Batukliang District, Central Lombok Regency. This street vendor activity was carried out from 15 July 2021 to 14 August 2021 in the ponds of Teratak Village, North Batukliang District, Central Lombok Regency. Data collection methods used are active participation, observation, and interviews. Data analysis used is descriptive analysis. This activity starts from pond preparation, media preparation, seed preparation, steroid application, herbs and probiotics, as well as water quality management. Management of Nirvana tilapia seed feed was given 3 times a day with 412 grams of feed for 21 days with feed mixed with steroid to masculinize or change the sex of tilapia from female to male. After 21 days, the fish fry were given a mixture of probiotics and herbs as much as 1.5 kg of feed for 11 seed pond plots. The stocking density per seed pond plot was 140,000 individuals, of the total stocking density, the number of fish that managed to reach nursery or grow-out was 110,000 individuals. The length of tilapia from the beginning of maintenance to 1 month of rearing is 2-3.5 cm. Quality management is carried out by adding probiotics, herbs and molasses 3 times a day according to weather conditions.